Woman New Century Theology - Beattie, Tina (London Continuum, 2003)
This theological investigation explores the significance of woman in the Christian tradition from various perspectives. It is written as an open-ended quest for meaning in the form of a "theopoetics" rather than as a systematically developed argument.
Keywords: Women -- Religious aspects -- Christianity. Feministische theologie. Vrouwen